Increasing Students' Understanding Of Conservation Using Learning Video Media Based On An Artificial Intelligence Platform - Hadi, Nestiyanto; Ainy, Noer Sarifah (UNIVERSITAS PAKUAN, 2024)
The Covid 19 pandemic has impacted many changes in various sectors of life, one of which is the education sector. There are many things that have changed significantly in the learning process in the world of education. Both in terms of learning activities, assessment processes and the development of learning media. One of them is the emergence of digital platforms that provide facilities to support the learning process. This digital platform is equipped with an Artificial Intelligence (AI) system in it. This research aims to help teachers improve their soft skills in creating interesting learning media videos with the help of an AI-based digital platform and determine its effect on increasing students' understanding of conservation. Based on the research results, it shows that the use of learning video media using AI can increase the value of student learning outcomes. This is shown by the results of statistical test calculations using a paired sample T test on the average value of the pre-test and post-test using AI learning videos which obtained a Sig value (0.001) 0.05, so that H0 is accepted and shows that there is a significant difference between the average values pre-test and post-test average. Meanwhile, the results of statistical tests in the control class without using AI learning videos obtained a Sig value (0.063) 0.05, so H0 was rejected and showed that there was no significant difference between the average pre-test and post-test scores. The use of learning video media can provide students with experience in being able to provide more concrete images related to conservation terms. That way, students can participate in learning activities optimally and be connected to the material presented by the teacher. The importance of this connection is so that students remain focused during learning activities.